The Effects of Vocabulary Learning on Taiwanese College Students’ Writing (Journal of NELTA, 2014)
This study investigates two approaches of vocabulary learning: productive and receptive and their effectiveness in facilitating Taiwanese college students’ writing. Participants were 99 first-year college students. One half was assigned to learn a set of 20 target words productively through word pairs and the other receptively. A post picture-based writing task was used to measure writing quality and the number of target words, and a vocabulary test, productive vocabulary knowledge. The results showed that the productive group outperformed the receptive group in writing quality, the number of target words and productive vocabulary knowledge. The findings suggest that productive vocabulary learning through word pairs may be more effective than the receptive method. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10330   Journal of NELTA, Vol 18 No. 1-2, December 2013; 53-64